The Relationship Between Family Support and Self-Care Management in Chronic Kidney Disease Patients Undergoing Hemodialysis at Sekarwangi Regional Public Hospital - Permatasari; Erna Safariyah; Amir Hamzah (PROFESSIONAL HEALTH JOURNAL, 2026)
This study aims to examine the relationship between family support and self-care management in Chronic Kidney Disease (CKD) patients undergoing hemodialysis at Sekarwangi Regional Public Hospital. A correlational research design with a cross-sectional approach was employed, involving 109 respondents. Data on family support were collected using the Perceived Social Support-Family (PSS-Fa) questionnaire, while self-care management was assessed using a self-care management scale. Descriptive and bivariate analyses were performed to analyze the data. The results indicated that 78.9% of respondents received good family support, and 91.7% demonstrated good self-care management. Statistical analysis using Fisher’s Exact Test showed a significant relationship between family support and self-care management (p = 0.019). Patients with good family support were more likely to have better self-care management (95.3%) compared to those with insufficient family support (21.7%). This study highlights the critical role of family support in enhancing patient confidence and adherence to self-care practices, which contributes to better management of CKD and improved quality of life. The findings suggest that strengthening family involvement in care could significantly improve the self-care management of CKD patients undergoing hemodialysis. Further interventions to enhance patient education and family support are recommended to optimize health outcomes for CKD patients.